Screening for optimum concentrations of boron, copper and manganese for the growth of three-month old oil palm seedlings in solution culture - Tengoua, Fabien Fonguimgo; Musa, Mohamed Hanafi; Abu Seman, Idris; Syed Rastan, Syed Omar (Universiti Putra Malaysia Press, 2015)
Micronutrient application has been in general overlooked in oil palm fertilisation programmes. Considering the importance of a balanced fertiliser in plant nutrition, it was necessary to determine the requirements of important micronutrients for their further recommendation in oil palm fertilisation programmes to ensure better growth and good yield. An experiment was conducted to identify the optimum concentrations of B, Cu and Mn for the growth of oil palm seedlings. The concentrations tested were 0, 0.25, 0.50, 1 and 2 mg B /L; 0, 0.5, 1, 2 and 4 mg Cu /L; 5, 10, 15 and 20 mg Mn /L. Germinated oil palm seeds were supplied with different concentrations of the selected micronutrients for three months in soilless culture. The assessment of the growth and physiological parameters showed that 2 mg/L for both B and Cu gave better response, while all the tested Mn concentrations were suppressive to the growth of oil palm seedlings. Therefore, 2 mg/L for both B and Cu and a minimal concentration of 2 mg Mn/L are being tested in new experiments in single and different possible combinations on nutritional, biochemical and growth parameters of oil palm seedlings from two to eight months for their future incorporation in oil palm fertilisers.